PENERAPAN LIBRARY 2.0 PADA PERPUSTAKAAN FAKULTAS TEKNIK UNIVERSITAS PALANGKA RAYA - Viktor Handrianus Pranatawijaya; Edi Rusadi (Universitas Palangka Raya, 2014)
Advancement technology online information by website can be infrastructure to user of library withcomunication each other member to library with make relationship of sociality, and will provideinformation to user as point of picture about Library. Yet in this modern era is in need of library usersinfomasi about books (catalogs) available to a library and lack of access to public information couldhamper the development of the library. With the increasing number of Internet users, it should be animportant factor for the Library of the Faculty of Engineering, University of Palangkaraya to maximizethe use of Internet media, especially websites to improve the dissemination of information as a form ofpublic service in accelerating the delivery of information.The study design is made consists of three stages: ( 1 ) data collection and analysis is done bymeans of literature study and observation , ( 2 ) applying the waterfall method which has been modifiedwith the stages are systems analysis to determine access rights along facilities , UML and ERD are made,the design of the system by doing database design, navigation structure, the implementation of the systemis done with programming language PHP, the database used is MySQL, Asynchronous Javascript andXML (Ajax), JQuery, HTML5 dan CSS3, and testing systems used black box testing, and ( 3 ) the resultsof research in which a web-based Library 2.0 that was made into a ready-made software .Conclusion of this thesis is to providing website menus to means of information. Users of thewebsite consists of : administrator, head of the library, library members and library members. As ameans of interaction, this website provides facilities for members of the library like facilities forums as amedium to communicate with the chat facility send photos and videos and exchanging information,whereas for non members of the library can only view the website. In future is expected to be added inthe form of multimedia, video learning, E-Paper and E-Book that is more appropriate to view the websitefor the better